Avengers : Destiny Arrives - Palmer, Liza (Los Angeles : Marvel, 2019)
After years of battling threats on Earth and across the universe, the Avengers, Guardians of the Galaxy, protectors of the Sanctum Sanctorum, and forces of Wakanda must join together to fight Thanos. The Mad Titan has collected all six Infinity Stones, and Doctor Strange has foreseen there is only one possible timeline that results in good prevailing over evil. It all comes down to this last battle... as destiny arrives. -- adapted from jacket
Keywords: Thanos -- (Fictitious character from Marvel Comics Group) -- Fiction; Avengers (Fictitious characters) -- Fiction; Guardians of the Galaxy (Fictitious characters) -- Fiction; Superheroes -- Fiction; Science fiction